Quelle est la relation entre les troubles musculo-squelettiques (TMS) liés au travail et les facteurs psychosociaux ? - Susan Stock; Nektaria Nicolakakis; Karen Messing; Alice Turcot; Hicham Raiq (Perspectives Interdisciplinaires sur le Travail et la Santé)
The scientific literature increasingly recognizes the multifactorial origin of non-traumatic, work-related musculoskeletal disorders (WMSD). Beyond the contribution of biomechanical and personal factors, many organizational and psychosocial factors have been suggested to contribute to the development of WMSD, but the interrelations between these health outcomes and work exposures seem complex and remain largely uncharacterized. Moreover, there is no common definition of the organizational and psychosocial work environment and of psychosocial workplace factors. Our research group addressed these questions. This article describes examples of the evolving conceptualization of health-related, psychosocial workplace factors in the last 30 years. A conceptual model of the development of WMSD is then presented that incorporates the authors’ vision of the psychosocial work environment and the possible mediating role of psychological distress.